Analisis Kegiatan Ekspor Kopi Indonesia Dalam Pasar Global - Yandi Suprapto; Erni Astuti (Program Pascasarjana STIE Amkop Makassar, 2023)
Export is an activity that can help boost a country's economy. Indonesia is the 4th largest country in the world as a coffee exporter. The purpose of this study was to determine the competitiveness of Indonesian coffee exports in international trade in the global market using the RCA (Revealed Comparative Advantages) analysis method. This research was conducted on five main countries that imported coffee from Indonesia, namely the United States, Egypt, Germany, Japan and Malaysia. After analysis, it can be concluded that the competitiveness of Indonesian coffee exports in the global market is relatively stable and good considering that the average RCA calculation results are above number 1 (> 1), which means that Indonesian coffee exports are able to compete and have strong competitiveness against other exporters. Keywords: Coffe, Export, International, RCA